Microthermometric fluid inclusion data and 87Sr/86Sr in hydrothermal precipitates from the NW Caldera and Upper Caldera vent sites, Brothers volcano - Diehl, Alexander; de Ronde, Cornel E J; Bach, Wolfgang (PANGAEA, 2020)
This dataset contains the rawdata of a microthermometric study of fluid inclusions in hydrothermal precipitates and 87Sr/86Sr composition of their host sulfate minerals. The samples were recovered at Brothers volcano, originate from the NW Caldera and the Upper Caldera vent sites and were retrieved during RV Sonne cruise SO253 in December 2016/January 2017 and during RV Thompson cruise TN350 in March 2018. The fluid inclusion dataset contains >400 measurements of ice melting temperatures, >340 measurements of homogenization temperatures and includes a detailed descriptions of the measured fluid inclusions. The 87Sr/86Sr dataset contains Thermal Ionization Mass Spectrometry (TIMS) measurments of 5 single crystal and 6 bulk samples of the fluid inclusion (sulfate) samples or material taken in direct adjacency.